LINE-1 Hypomethylation in a Choline-Deficiency-Induced Liver Cancer in Rats: Dependence on Feeding Period. (6th March 2006) - Asada, Kiyoshi; Kotake, Yashige; Asada, Rumiko; Saunders, Deborah; Broyles, Robert H.; Towner, Rheal A.; Fukui, Hiroshi; Floyd, Robert A.
Abstract : Chronic feeding of methyl-donor (methionine, choline, folic acid, and vitamin B12) deficient diet induces hepatocellular carcinoma formation in rats. Previous studies have shown that promoter CpG islands in various cancer-related genes are aberrantly methylated in this model. Moreover, the global genome in methyl-donor-deficient diet fed rats contains a lesser amount of 5-methylcytosine than control livers. It is speculated that more than 90% of all 5-methylcytosines lie within the CpG islands of the transposons, including the long/short interspersed nucleotide elements (LINE and SINE). It is considered that the 5-methylcytosines in LINE-1 limit the ability of retrotransposons to be activated and transcribed; therefore, the extent of hypomethylation of LINE-1 could be a surrogate marker for aberrant methylation in other tumor-related genes as well as genome instability. Additionally, LINE-1 methylation status has been shown to be a good indicator of genome-wide methylation. In this study, we determined cytosine methylation status in the LINE-1 repetitive sequences of rats fed a choline-deficient (CD) diet for various durations and compared these with rats fed a choline-sufficient (CS) diet. The methylation status of LINE-1 was assessed by the combined bisulfite restriction analysis (COBRA) method, where the amount of bisulfite-modified and RsaI-cleaved DNA was quantified using gel electrophoresis. Progressive hypomethylation was observed in LINE-1 of CD livers as a function of feeding time; that is, the amount of cytosine in total cytosine (methylated and unmethylated) increased from 11.1% (1 week) to 19.3% (56 weeks), whereas in the control CS livers, it increased from 9.2% to 12.9%. Hypomethylation in tumor tissues was slightly higher (6%) than the nontumorous surrounding tissue. The present result also indicates that age is a factor influencing the extent of cytosine methylation.